HUBUNGAN SENAM VITALISASI OTAK DENGAN KUALITAS TIDUR LANJUT USIA DI WILAYAH PUSKESMAS RAPAK MAHANG TENGGARONG - Ramdhany Ismahmudi (Universitas Muhammadiyah Kalimantan Timur, 2017)
Background: Elderly generally will be less and less ability to sleep 5 to 8 hours (Lumbantobing, 2004), did not achieve adequate sleep quality and will give rise to a wide range of sleep complaints (Marcel, 2008). One non-pharmacological therapy is to exercise regularly through exercises vitalization of the brain. But not yet known vitalization brain gymnastics relationship with sleep quality in the elderly.Methodology: This study is descriptive correlational research with cross sectional approach. The purpose of this study was to determine the relationship gymnastics vitalization of the brain with sleep quality in the elderly. The study population was elderly aged 55-64 years residing in Puskesmas Rapak Mahang who regularly follow the gymnastics of the brain in 13 Posyandu revitalization, as many as 454 people. The sampling technique used was quota sampling by 33 elderly. Sleep quality was measured by The Pithburg Sleep Quality Index (PSQI) and gymnastics measured by observation sheet.Results: Characteristics of respondents are mostly have female gender (68.7%), aged 57 years, and the majority (66.7%) no activity other than gymnastics vitalization olehraga large otak.Sebagian elderly (66.7%) vitalization of the brain has been doing gymnastics done well. Most of the good sleep quality (66.7%) and a small fraction of less good.There relationship between gymnastics vitalization of the brain with sleep quality (p value 0.017; α: 0.05). Conclusions and Recommendations: Gymnastics vitalization of the brain is useful in improving the quality of life of the elderly. It is recommended that the elderly to follow this with a vitalization gymnastics routine, appropriate movement instructors, increase the frequency of exercises 2 times a week.